A graph representation model for radiation exposure prediction and path-planning in nuclear power plants. (15th June 2021) - Li, Mengkun; Xu, Zhihui; Yang, Jun; Yang, Ming
Highlights: A Graph representation model is developed to characterize and simplify NPP. Based on radiation zoning, radiation dose prediction method is proposed. The radiation safety of operators can be optimized by path panning in the building of NPP. The graph representation model with the ichnography can intuitively indicate the route for navigation. Abstract: In recent years, it is often seen that digital platform has been used for scenario simulation and safety assessment of nuclear industry. We propose a graph representation model (GRM) to characterize and simplify a Nuclear Power Plant (NPP) for digital simulation. Based on the GRM and the radiation zoning in NPPs, a radiation exposure prediction method is proposed for pre-evaluating cumulative dose of onsite operator. The onsite operator's occupational safety and efficiency can be improved by path-panning in NPPs. Based on GRM, we propose a path-planning algorithm for obtaining the optimum path from all possible paths. The GRM and the ichnography of NPP can be combined for indoor navigation in digital platform of nuclear industry. The simulation results show that the GRM of NPP is feasible for radiation exposure prediction and path-planning for onsite operators, and the GRM has potential for application in different situations, such as nuclear operation, nuclear decommissioning and nuclear emergency, and nuclear security.